Defaults and Donations: Evidence from a Field Experiment - Altmann, Steffen; Falk, Armin; Heidhues, Paul; Jayaraman, Rajshri; Teirlinck, Marrit (The Review of Economics and Statistics, 2019)
Abstract We study the effects of defaults on charitable giving in a large-scale field experiment on an online fundraising platform. We exogenously vary default options along two choice dimensions: the charitable donation decision and the “co-donation” decision regarding how much to contribute to supporting the platform. We document a strong effect of defaults on individual behavior but nevertheless find that aggregate donation levels are unaffected by defaults. In contrast, co-donations increase in the default amount. We complement our experimental results with a structural model that investigates whether personalizing defaults based on individuals' donation histories can increase donation revenues.